Biocatalysis in ionic liquids: enzymatic synthesis of sugar fatty acid esters - Silvério, Sara Isabel Cruz (2020)
Sugar fatty acid esters (SFAEs) are composed of one or more fatty acid chains linked to a carbohydrate molecule. They are commonly used as non-ionic and biodegradable surfactants and emulsifiers. However, SFAEs also present other interesting features such as tasteless, odorless, non-toxicity, and bioactivity which make them suitable for industrial applications in the food, pharmaceutical, and cosmetics industries. Traditionally, SFAEs are obtained from chemical synthesis despite the recognized disadvantages associated to this process. More recently, the synthesis of SFAEs using enzymes as biocatalysts proved to be a suitable and greener alternative. However, the use of organic solvents as reaction medium has been pointed out as one of the greatest limitations of the enzymatic process. To overcome this issue, ionic liquids (ILs) have been proposed as alternative solvents. ILs are frequently described as ``tunable'' solvents due to the possibility of combining different cations and anions to obtain the desired physicochemical properties. Based on their unique characteristics, ILs have been recognized as suitable solvents for biocatalytic processes involving different enzymes and reactions. Nevertheless, the selection of the suitable IL for the enzymatic synthesis of SFAEs is considered a key aspect in the bioprocess since compounds chemically different (sugars, fatty acids, and enzymes) are simultaneously present in the reaction medium. Ideally, the IL used as solvent should facilitate the solubilization of the substrates and not negatively affect the enzymatic activity and stability. The enzymatic synthesis of SFAEs can occur though two different approaches, namely esterification and transesterification. Several ILs and biocatalysts have been successfully reported for the synthesis of different types of SFAEs. Considering the enormous versatility of combining different sugars with fatty acids, it is expected that novel and promising SFAEs could be synthesized in the future using ILs as reaction medium.